2018
DOI: 10.18632/oncotarget.23589
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia predicts poor prognosis of patients with cervical cancer

Abstract: Previous studies have suggested that hyperuricemia plays an important role in cancer initiation and progression; however, little is known about the role of hyperuricemia in the prognosis of cervical cancer. The aim of this study was to evaluate the association between hyperuricemia and cervical cancer by conducting a retrospective cohort study. 50 cervical cancer patients with hyperuricemia were randomly selected and 1:1 age-matched to 50 normouricemia patients with cervical cancer. We used the Kaplan-Meier su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In multinomial regression analysis, uric acid showed a 1.23 odds ratio for HPV-ve and the adjusted odds ratio was 1.46 folds while for HPV + ve patients it increased from 1.30 to 1.53 folds crude to adjusted odds ratio in comparison to healthy women. Two groups have independently reported that hyperuricemia is a major metabolic indicator for the poor prognosis of CaCx [29,52]. Although uric acid possesses antioxidant properties but its increased level leads to chronic and systematic in ammatory responses in the human body and thus promotes tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In multinomial regression analysis, uric acid showed a 1.23 odds ratio for HPV-ve and the adjusted odds ratio was 1.46 folds while for HPV + ve patients it increased from 1.30 to 1.53 folds crude to adjusted odds ratio in comparison to healthy women. Two groups have independently reported that hyperuricemia is a major metabolic indicator for the poor prognosis of CaCx [29,52]. Although uric acid possesses antioxidant properties but its increased level leads to chronic and systematic in ammatory responses in the human body and thus promotes tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported the association of metabolic-related factors including lipid, urea, creatinine, and uric acid with tumor prognosis and tumorigenesis [25]. Uricemia is the result of abnormal uric acid metabolism which has been associated with pathogenesis of various diseases like gout [26], cardiovascular diseases (CVD) [27], pulmonary diseases [28], and cancer [29]. Although serum uric acid possesses antioxidant properties, increased levels can lead to in ammation and promote tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that metabolic by-products and related factors play an important role in cancer development, incidence, diagnosis, and prognoses like dyslipidemia and hyperuricemia [14]. Impairment of uric acid leads to hyperuricemia and it is involved in the physiopathogenesis of gout, cardiovascular diseases, respiratory diseases, and cancer [15].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported the association of metabolic-related factors including lipid, urea, creatinine, and uric acid with tumor prognosis and tumorigenesis [14]. Uricemia is the result of abnormal uric acid metabolism which has been associated with pathogenesis of various diseases like gout [15], cardiovascular diseases (CVD) [16], pulmonary diseases [17], and cancer [16].…”
Section: Introductionmentioning
confidence: 99%